Transmisi Kebijakan Moneter di Indonesia: Credit View atau Money View? - Safuan, Sugiharso; Laksono, Beta Yulianita G. (UI Scholars Hub, 2007)
One of some problematic issues of identification of the effectiveness of the monetary policy is the question on whether the monetary policy mechanism transmissions can perform fully in transmitting the changes of monetary policies into the national and regional level of economy. On earlier studies, Muelgini (2004) relatively compares the effectiveness of monetary policies of the five mechanism transmission channels at the national level of the economy employing impulse response function. The results show that prior to the economic crises in Indonesia credit channel is not effective, and for after crises periods interest rates, credit, and asset price channels are becoming relatively important. Utilizing similar methodology, Laksono (2005) finds that the effectiveness of monetary mechanism varies among regions. This research analyzes the findings of both Muelgini's and Laksono's employing different methodology to evaluate the channels through which monetary policies are transmitted.